2010
DOI: 10.1021/jz100027t
|View full text |Cite
|
Sign up to set email alerts
|

Direct Water Splitting Through Vibrating Piezoelectric Microfibers in Water

Abstract: We propose a mechanism, a piezoelectrochemical effect for the direct conversion of mechanical energy to chemical energy. This phenomenon is further applied for generating hydrogen and oxygen via direct water decomposition by means of as-synthesized piezoelectric ZnO microfibers and BaTiO3 microdendrites. Fibers and dendrites are vibrated with ultrasonic waves leading to a strain-induced electric charge development on their surface. With sufficient electric potential, strained piezoelectric fibers (and dendrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
271
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(279 citation statements)
references
References 15 publications
5
271
0
3
Order By: Relevance
“…In addition to the PEC devices, Hong et al showed that a piezoelectric potential could also be implemented to drive the nonspontaneous water splitting reaction [561]. The working principle is shown in Fig.…”
Section: Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the PEC devices, Hong et al showed that a piezoelectric potential could also be implemented to drive the nonspontaneous water splitting reaction [561]. The working principle is shown in Fig.…”
Section: Water Splittingmentioning
confidence: 99%
“…Schematic diagram showing that by bending under ultrasonic vibration, the charges and piezopotential developed on a piezoelectric material, such as a ZnO fiber, can drive the splitting of water into oxygen and hydrogen [561]. Reproduced with permission…”
Section: Figure 69mentioning
confidence: 99%
“…It was shown recently that following this approach an electrostatic potential large enough to facilitate electrolysis of water molecules can develop even in liquid phase. 13 Applying ultrasonic vibration to piezoelectric, substrate-supported, fibrous ZnO and dendritic BaTiO 3 materials generated H 2 and O 2 in stoichiometric ratio. The authors have termed this phenomenon the piezoelectrochemical effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently there have been investigations into the use of dynamic applications, where a piezoelectric material is continuously and alternately strained between a tensile and compressive state resulting in a large and rapidly varying piezoelectric field within the material. This continuously varying system is prevented from achieving thermodynamic (electrochemical) equilibrium with its environment, the result of which is an enduring, though fluctuating, exchange of charge between the piezoelectric and its environment [6,7,29,30].…”
Section: Piezopotential-driven Electrochemistrymentioning
confidence: 99%
“…One such heterojunction that is particularly dynamic is that which exists between a piezoelectric material and a chemical solution [6,7]. Piezoelectric fields have been used to control the corrosion rate of materials exposed to etchant solutions [8][9][10][11][12][13][14][15][16][17][18], selectively control the energetics and spatial separation of adsorbed [19,20] and photo-deposition materials [21][22][23][24][25][26][27][28], and have even been used to directly drive electrochemical reactions across piezoelectric/solution interface [6,7,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%